The association between development assistance for health and malaria, HIV and tuberculosis mortality: A cross-national analysis - Allan J. Hsiao; Connor A. Emdin (Springer, 2019)
Development assistance for health (DAH) and foreign aid have been criticized for being poorly associated with health and economic outcomes on a national level. This study is an attempt to examine whether DAH targeted specifically to malaria, HIV and tuberculosis (TB) is associated with changes in malaria, HIV and TB mortality, respectively. A dataset of DAH targeted to malaria, HIV and TB and corresponding malaria-, HIV- and TB-specific mortality was compiled for 120 low- and middle-income countries. Regression analysis was performed using country and time-period fixed effects and control variables. While malaria and HIV DAH were associated with reductions in malaria and HIV mortality, respectively, TB DAH was not significantly associated with reductions in TB mortality. Estimates were consistent in various sensitivity analyses, including generalized method of moments estimation, addition of extra controls and analysis of a multiply imputed dataset. In conclusion, targeted DAH is associated with reduction of HIV and malaria mortality on a national level.